Who's About to Leave? A Global Survey of Aspirations and Intentions to Migrate. (15th August 2019) - Migali, Silvia; Scipioni, Marco
Abstract: This article analyses aspirations and intentions to migrate based on Gallup World Poll for the period 2010–2015. We estimate individual‐level traits associated with aspirations and intentions to migrate across groups of countries in different regions and with different income levels. This paper brings together previous hypotheses regarding migration aspirations and tests them under several specifications, while keeping separate findings according to migration aspirations and intentions to appreciate differences between them. Being dissatisfied with one's own standard of living is associated with a higher probability of desiring to move, while the relation with the actual preparation to migrate is less clear. Some individual traits remain significant across (almost) all specifications: being male, foreign‐born, highly educated, and having networks abroad are associated with higher probability of preparing for international migration. Aspects related to one's economic situation are not consistently significant across specifications, signalling the importance of contextual analyses for these factors.